Sobre la importancia de la certificación internacional para los anilladores de aves en Perú - Díaz, Alexis (2019)
Certification as bird bander implies to validate the level of knowledge and experience of people with regard to a consolidated standard of work in the exercise of capture, banding, handling, and release of birds, in order to promote the safety of the bird, the security of the bander and the quality of the data collected. The North American Banding Council (NABC) is a non-profit organization that includes diverse organizations of research, conservation and management of North American avifauna. Continuing with its mission to promote responsible bird-banding practices under standardized and ethical criteria, in a joint effort with the Centro de Ornitologia y Biodiversidad (CORBIDI) and other related institutions, the first three NABC certification sessions were recently held in Peru. This work tries to answer some of the most frequent questions related to these certification events and the bird banding efforts promoted by the Programa de Anillamiento CORBIDI (PAC).